2004
DOI: 10.1002/anie.200301690
|View full text |Cite
|
Sign up to set email alerts
|

Trigonal Prismatic or not Trigonal Prismatic? On the Mechanisms of Oxygen‐Atom Transfer in Molybdopterin‐Based Enzymes

Abstract: Nature is versatile and can make use of even seemingly exotic bonding situations. Recent quantum chemical evidence suggests trigonal‐prismatic intermediates and transition states occur in oxygen‐atom transfer catalysis of molybdopterin‐based enzymes from the DMSO reductase family (see structure, green C, yellow S, blue N, red O, white H). This Highlight presents the fascinating theoretical and experimental findings within the general framework of “non‐VSEPR” structures of d0–d2 transition metal complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…7,10-15, 17,18 In particular, the importance of the trigonal prismatic structure has been emphasized, 61 as well as the fact that the enzyme seems to destabilize the product by avoiding a octahedral structure.…”
Section: Structuresmentioning
confidence: 99%
“…7,10-15, 17,18 In particular, the importance of the trigonal prismatic structure has been emphasized, 61 as well as the fact that the enzyme seems to destabilize the product by avoiding a octahedral structure.…”
Section: Structuresmentioning
confidence: 99%
“…[62] Enzymes of the xanthine oxidase family catalyze hydroxylation reactions of several substrates, and the mechanism proposed implies a trigonal-prismatic intermediate in which the substrate is coordinated to a molybdenum atom, [63] whose geometry is supported by computational studies. [64] Several copper sites present coordination environments that are described as intermediate between the trigonal prism and the octahedron, including a copper amine oxidase, [65] copper-substituted human lactoferrin, [66] and superoxide dismutases, [67] although their deviations from the Bailar pathway are quite large. Also the environment of the Fe atom in enterobactin has a twisted geometry that, however, is closer to the octahedron than to the trigonal prism (see the Supporting Information), while the vanadium(IV) enterobactin complex [68] is practically midway between the octahedron and the trigonal prism (f OC!TP = 54 %).…”
Section: Occurrence and Relevance Of The Trigonal Prism As A Coordinamentioning
confidence: 99%
“…A second-shell residue, Glu869, forms one hydrogen bond to the oxygen species bound to Mo. The reaction mechanisms of Mo-AOR [34], xanthine oxidase [35][36][37][38][39][40][41][42][43][44], and other related Modependent enzymes [45][46][47][48][49][50][51][52][53] have been studied using quantum chemical methods. Recent QM/MM calculations of Mo-AOR suggested that the Glu869 residue functions as a general base to take a proton from the Mo-OH and to facilitate nucleophilic attack on the substrate aldehyde carbonyl carbon to form a tetrahedral intermediate [34].…”
Section: Introductionmentioning
confidence: 99%